The provision of public goods with positive group interdependencies - Werner Güth; Lauri Sääksvuori (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
This article examines the nature of human behavior in a nested social dilemma referred to as the Spillover Game. Players are divided into two groups with positive production interdependencies. Based on theoretically derived opportunistic, local, and global optima, our experimental results demonstrate the importance of in-group beneficiaries over global efficiency. We find that the observed behavior is primarily determined by an imperfect conditional cooperation that prioritizes local level feedback. Results stress the importance of building strong local level commitment to encourage the provision of public goods with positive externalities.
Keywords: H41; C72; C91; C92; 330; Public good; experiment; groups; Spillover Game; social dilemma; Öffentliches Gut; Gefangenendilemma; Soziale Beziehungen; Spillover-Effekt; Test